A: Alpha-Activity of Natural Samarium B: A Search for Neutronic Nuclei - Gupta, Moolchand (My University, 1967)
The alpha-activity of natural samarium has been studied using an ionization chamber. A gridless ionization chamber has been developed in order to obtain high resolution and high sensitivity. The half lives and the energies of the alpha decay of Sm147 and Sm148 were measured where as the alpha-activity of Sm149 and Sm146 could not be detected.
Experiments were carried out in order to search for the existence of Particle stable neutron clusters in the range of Mass 6-10 as a component of a nuclear reactor flux and as the product of high energy proton spallation of heavy nuclei.
Keywords: alpha-activity, samarium, neutronic, nuclei, energy, decay